Answer: C
Step-by-step explanation:
-3x=36
Divide -3 by both sides
x=-12
59×2=118 cost of bill.
59÷4=14.75 for the other 4 if the bill was 118 assuming Thomas pays half.
or...59 ×5=295
assuming they all pd 1/5 of the bill
Answer:
i needd points sorry
Step-by-step explanation:
nts
M² - 12m + 20
m² ⇒ m * m
20 ⇒ - 10 * -2
(m - 10)(m - 2)
m(m - 2) - 10(m-2)
m² - 2m - 10m + 20
m² - 12m + 20
m - 10 = 0
m = 10
m - 2 = 0
m = 2
Answer:
Option C - Simplify the right side using the "difference of two logs is the log of the quotient" property.
Step-by-step explanation:
Given : Expression
To find : What is the first step in solving the expression ?
Solution :
Expression
Step 1 - Simplify the right side using the "difference of two logs is the log of the quotient" property.
i.e.
Apply the first step we get,
Therefore, Option C is correct.